Changing Face of Movie Marketing in India: A Case Study - Agarwal, P. K; Kumar, Pradeep; Gupta, Swati (Journal of Commerce and Trade, 2012)
Gone are the days when plastering a few posters on the walls and hand-painted billboard signs though very attractive were the only means available for a movie’s marketing. Actors barely promoted their movies as is happening today, movie-producers never ventured in front of the camera and our main stream media didn’t care. Today’s Bollywood presents a very different scenario. With over one thousand movies releasing in a year and all of them fighting for a common goal i.e. box-office success. For the success of the movie it has become a imperative necessity for those involved, to do whatever it takes to enforce that “must-watch” feeling among the masses in order to win the hearts of masses & classes and to move through this very competitive rat-race. In this marketing, the Indian media played a vital role. This paper discusses the concept of movie marketing and how the different marketing channels are used to create not just awareness but also increase the saleability of the finished product i.e. the movie. This paper of ours highlights on the questions, What is the formula for successful movies? How do movies manage to keep the cash register moving? What do the audiences want? Though there are no definite answers to these questions, though there are formulas or mavericks which have been reasonably figured out by successful directors in the different eras of moviemaking.